THE ROLE OF BAITUL MAAL WA TAMWIL BMT UGT NUSANTARA BRANCH OF RAAS DISTRICT IN IMPROVING THE PERFORMANCE OF UMKM - Ahmad Zainullah; Hadi Sunaryo; Muhammad Agus Salim (Pena Cendekia Insani, 2025)
This study focuses on the role of Baitul Maal wa Tamwil (BMT) UGT Nusantara, Raas Sub-district Branch Office in improving the performance of Micro, Small, and Medium Enterprises (MSMEs) in the archipelago that have limited access to conventional financing. The research method used is qualitative with a case study approach, which allows for an in-depth understanding of the socio-economic context and local characteristics through in-depth interviews, participatory observation, and documentation. Data analysis was carried out using the Miles and Huberman technique which includes data reduction, presentation, and verification. The results of the study indicate that BMT UGT Nusantara not only provides sharia-based financing through the Modal Usaha Barokah (MUB) program with the Rahn contract, but also provides mentoring and entrepreneurship education that significantly increases the managerial capacity and productivity of MSMEs. The success of BMT in encouraging increased income and expansion of MSME businesses cannot be separated from the support of social capital and the active role of the sub-district government. The implications of this study emphasize the importance of Islamic microfinance institutions as agents of holistic local economic empowerment, as well as the need to develop integrated financing programs with assistance to ensure the sustainability and inclusiveness of MSME growth in remote areas.